Effect Yoga on Health-Related Quality of Life in Menopause Women - Lulut Khoridatur Rosida; Sinu Andhi Jusup; Bhisma Murti (Nexus Kedokteran Komunitas, 2017)
Introduction: Menopause causes changes in ovarian function that will automatically affect production of hormones that can cause a variety of physical and mental symptoms. These symptoms will lead to lower health-related quality of life in postmenopausal women. Yoga is a physical and meditation exercise. According to various studies, yoga can reduce symptoms of postmenopausal syndrome. This study aimed to investigate effect yoga on health-related quality of life in menopause. Methods: This research used observational analytic with case control approach. The subject were postmenopausal women who did yoga in Ganep's Surakarta. Samples were taken with fixed exposure sampling technique. There were 45 subjects of research which consists of 15 people did yoga and 30 people did not yoga. Independent variable of this research was yoga and dependent variable was health-related quality of life scores were measured using a questionnaire Medical Outcomes Study SF-36. Gained Data was presented in table form and analyzed bivariate analysis using t-test and multivariate analysis using multiple linear regression analysis. Results: This research showed t-test value p < 0.001 which meant that there was significant effect yoga on health related quality of life. And there were significant difference scores between yoga group and no yoga group (p < 0.001). Multiple linear regression value showed regression coefficients= 435,6; p < 0.001 (Constants: 3296.41; CI 95% (-692)-1230.82; R2adjusted: 32.2% and p < 0.001). Conclusions: Yoga can effect on health-related quality of life in menopause women. Keywords: Yoga, Quality of life, Menopause.